2010
DOI: 10.1038/nrcardio.2010.50
|View full text |Cite
|
Sign up to set email alerts
|

Strategic choices to reduce implantable cardioverter-defibrillator-related morbidity

Abstract: The indications for ICD implantation continue to expand; however, these devices are associated with complications related to the implantation procedure itself and morbidity caused by the normal and abnormal functioning of the components comprising the system. Several factors need to be considered when embarking on initiating ICD implantation. Special consideration should be given to implantation technique and choice of operator to decrease acute complications. After implantation, the device should be appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The groundwork for this study includes the primary prevention parameters evaluation trial (PREPARE2), pacing fast ventricular tachycardia reduces shock therapies (PAINFREE RX II) [8], and comparison of empiric to physician-tailored programming of implantable cardioverter-defibrillators (EMPIRIC) [9] trials, which demonstrated reduced appropriate shocks and no increase in mortality with programming strategies. Five programming strategies in the PREPARE trial reduce ICD shocks [2,10] (see list below). In MADIT-RIT, high detection rate and delayedtherapy programming significantly reduced appropriate and inappropriate therapy when compared with conventional programming (Table 1).…”
Section: Implantable Cardioverter-defibrillator Programming To Minimimentioning
confidence: 99%
See 1 more Smart Citation
“…The groundwork for this study includes the primary prevention parameters evaluation trial (PREPARE2), pacing fast ventricular tachycardia reduces shock therapies (PAINFREE RX II) [8], and comparison of empiric to physician-tailored programming of implantable cardioverter-defibrillators (EMPIRIC) [9] trials, which demonstrated reduced appropriate shocks and no increase in mortality with programming strategies. Five programming strategies in the PREPARE trial reduce ICD shocks [2,10] (see list below). In MADIT-RIT, high detection rate and delayedtherapy programming significantly reduced appropriate and inappropriate therapy when compared with conventional programming (Table 1).…”
Section: Implantable Cardioverter-defibrillator Programming To Minimimentioning
confidence: 99%
“…In MADIT-RIT, high detection rate and delayedtherapy programming significantly reduced appropriate and inappropriate therapy when compared with conventional programming (Table 1). ICD programming strategies to reduce shocks are given below [2,10]: We believe that ICD programming to minimize both appropriate and inappropriate ICD shocks can play an important role in improving patient outcomes.…”
Section: Implantable Cardioverter-defibrillator Programming To Minimimentioning
confidence: 99%
“…Furthermore, though not as wellstudied as rates and risk factors, the cost consequences of TV lead complications appear to be considerable, with estimates of the episodic costs of reoperation in the United States (US) ranging from $25 000 to more than $100 000 depending on the presence of infection and other factors. 5,[7][8][9][10][11] Not surprisingly, attention has thus focused on strategies to improve prevention 12 The objectives of this study were to estimate the direct medical costs to Medicare associated with TV lead reoperation, describe patterns of complications around lead reoperation, and examine the impact of complications on medical resource use and costs.…”
Section: Introductionmentioning
confidence: 99%
“…32 Adding a defibrillator-cardioverter device to CRT is a related and sometimes difficult issue because of inappropriate shocks. 27 Although these factors may be less important in patients with advanced HF undergoing CRT, the overall favorable survival rates in a large majority of patients with mild HF are a cause for concern if the initial estimates of risk in regard to CRT rise beyond the observation periods in MADIT-CRT or REVERSE (ie, Ͼ2.5 years on average).…”
Section: Is the Risk Of Crt Equal To That Of An Implantable Cardiovermentioning
confidence: 99%
“…This is particularly true when older patients (often excluded from clinical trials) may have a wide range of complications related to device implantation. 26 Seldom discussed are the late complications of device implantations including device infections, lead malfunctions, and inappropriate device programming, 27 all of which can raise concerns in less sick individuals in whom the relative benefits are far lower than in sicker individuals. In the clinical practice setting, adding 1 or even 2 leads can extend procedure time and may directly add to the risk.…”
Section: Is the Risk Of Crt Equal To That Of An Implantable Cardiovermentioning
confidence: 99%